Use of fungi to improve bioconversion of activated sludge - Mannan, Sarkar; Fakhru’l-Razi, A.; Alam, Md. Zahangir (Elsevier Science, 2005)
TThe present study was designed to evaluate the potential of microbial adaptation and its afﬁnity to biodegradation as well as bioconversion of soluble/insoluble (organic) substances of domestic wastewater treatment plant (DWTP) sludge(activated domestic sludge) under natural/non sterilized conditions. The two ﬁlamentous fungi, Penicillium corylophilum (WWZP1003) and Aspergillus niger (SCahmA103) were used to achieve the objectives. It was observed that P. corylophilum (WWZP1003) was the better strain compared to A. niger (SCahmA103) for the bioconversion of domestic activated sludge through adaptation. The visual observation in plate culture showed that about 95–98% of cultured microbes (P. corylophilum and A. niger) dominated in treated sludge after 2 days of treatment. In this study, it was also found that the P. corylophilum was capable of removing 94.40% of COD and 98.95% of turbidity of ﬁltrate with minimum dose of inoculum of 10% v/v in DWTP sludge (1% w/w). The pH level was lower (acidic condition) in the fungal treatment and maximum reduction of COD and turbidity was observed (at lower pH). The results for speciﬁc resistance to ﬁltration (SRF) showed that the fungi played a great role in enhancing the dewaterability and ﬁlterability. In particular, the strain Penicillium had a more signiﬁcant capability (than A. niger) of reducing 93.20% of SRF compared to the uninoculated sample. Effective results were observed by using fungal inoculum after 2 days of treatment. The developed LSB process is a new biotechnological approach for sludge management strategy.